REDUCING THE PERILS OF MERGING BOOLEAN AND WEIGHTED RETRIEVAL SYSTEMS - RADECKI, TADEUSZ (Journal of documentation, 1982)
A need for developing an information retrieval technique maintaining the appeal of Boolean retrieval schemes and in addition providing the advantages of a ranked search output has been pointed out in the literature for many years. However, a previous attempt to incorporate into the Boolean retrieval schemes a weighting mechanism to produce ranked lists of documents has not been fully successful. Specifically, further research has demonstrated that the theory behind the previous approach is characterized by disturbing ambiguities and inconsistencies, with equivalent Boolean search request formulations yielding different rankings of documents retrieved. As a result of this more recent research an alternative approach has been outlined. However, a closer analysis of this second approach reveals that it is also not free from some intrinsic weaknesses. The present paper provides the results of this new analysis and suggests a more rigorous methodology.